PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MUATAN IPA SDN DADAPREJO 01 KOTA BATU - Antonius Alam Wicaksono; Moh. Farid Nurul Anwar; Prisila Janelia (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to figured out how to use the Disclosure Learning model and improve understudy learning outcomes in science content (subject 6: Intensity and Move), sub-topic 1: Learning Temperature, and Intensity 1: Sources of Intensity Energy). As a method of research, classroom action research (CAR) is utilized. The teacher's ability assessment tools, namely APKG1 and APKG2, are used in cycles I and II in the Discovery Learning model implementation. In the assessment of theme 6: heat and its isolation, sub-theme 1: temperature and heat, and learning 1: heat energy sources with natural science content, scores for as many as 80% of class Vb students at SDN Dadaprejo 01 Batu City fell below the minimum completeness criteria (KKM). The average student learning outcomes for the Discovery Learning model with six sub-themes, one learning theme, and one science theme were 71.2 percent in cycle I and 82.2 percent in cycle II. Using APKG1 and APKG2, the average scores for cycle I was 73.52 and 84.09, respectively. In cycle II, the average value has increased from APKG1's 92.91 and APKG2's 96.58, respectively. This study shows that using the Discovery Learning model can improve student learning outcomes.